Queer Spaces, Africanness, and Bildung - Ntokozo Wandile Mbokazi; Lucy Valerie Graham (The Thinker)
The Quiet Violence of Dreams (2001) and Inxeba (The Wound) (2017) are post-apartheid texts that reveal the violence inflicted on queer Black bodies within a patriarchal and homophobic society, while also challenging heteronormative conceptions of Africanness and exploring potential spaces where Black queerness might exist. Each work also functions as a narrative of personal growth: The Quiet Violence of Dreams is a Bildungsroman, while Inxeba focuses on the coming-of-age process into manhood through an initiation ritual. As stories of development and initiation, both texts explore whether queer Black bodies can find a place within post-apartheid South African communities—or whether they remain excluded. Although both works have been widely discussed in academic circles, no prior study has examined them together. We contend that these two post-apartheid works can be compared in terms of heteronormative disciplinary violence, as well as in relation to themes of queerness and Africanness. This comparison raises additional questions about potential spaces for Black queerness in the aftermath of apartheid.